THE INFLUENCE OF DEBT TO EQUITY (DER), RETURN ON ASSET (ROA), PROFIT GROWTH, PRICE EARNING RATIO (PER) AND PRICE TO BOOK VALUE (PBV) ON STOCK PRICES IN EAST JAVA REGIONAL DEVELOPMENT BANK FOR THE QUARTERLY PERIOD 2013-2022 - Suci Fauziah Lestari; Yoyo Sudaryo; Andre Suryaningprang; Dadan Abdul Aziz; Mochammad Mukti Ali; Erna Herlinawati (Jurnal Scientia, 2023)
This research was conducted to determine the effect of Debt to Equity Ratio (DER), Return on Assets (ROA), Profit Growth, Price Earning Ratio (PER) and Price to Book Value (PBV) on Stock Prices in East Java Regional Development. Bank Quarterly Period 2013-2022. The research method used uses quantitative research methods with descriptive and verification approaches. The data source in this research is secondary data obtained through quarterly financial reports using a purposive sampling technique. Data analysis techniques use descriptive analysis techniques, verification analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing, both partial and simultaneous testing with data analysis tools using SPSS version 25. The results of this research partially show that Debt to Equity Ratio (DER), Return On Assets (ROA) and Price to Book Value (PBV) have a significant effect on Stock Prices, while Profit Growth and Price Earning Ratio (PER) do not have a significant effect on Stock Prices. while simultaneously all independent variables have a significant effect on stock prices.